Pengaruh Kualitas Pelayanan, Harga, dan Lokasi Terhadap Kepuasan Pelanggan pada Toko Ponsel Fortune Meulaboh - Hajar, Siti; Andika, Syahreza (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to use a quantitative approach to the phenomena that occur at the Fortune Meulaboh Mobile Phone Store. The Data Method used in this study is the Nonprobability Sampling technique with a Sample of 83 Customers who shop at the Fortune mobile phone store. The data used are Primary data and Secondary data. The data analysis techniques that will be used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis Test, Hypothesis Testing using SPSS22 Software and Determination Coefficient. The results of this test state that the Influence of Service Quality, Price and Location has an effect on Customer Satisfaction at the Fortune Mobile Phone Store.